Gender perspective and the role of universities in the XXI century - Inmaculada LÓPEZ-FRANCÉS; Victoria VÁZQUEZ VERDERA (Ediciones Universidad de Salamanca, 2015)
The article shows the emerging line of research and teaching being developed by the authors. It starts from the perceived needs of the students in two universities: the University of Valencia and the Autonomous University of the State of Morelos; data is collected through a questionnaire (designed ad hoc and validated) and several discussion groups. The performance of teachers is considered a catalyst in the construction of new identities and ethical professionals capable of meeting the challenges of the XXI century. It explores and identifies some challenges to allow the development of teaching, research and management free of gender bias. It concludes by recognizing the interdependence and the need to care for cooperative action and networking in order to enable sustainable, equitable and reciprocal human development.